PEMANFAATAN SNELLEN CHART OLEH GURU-GURU UKS UNTUK DETEKSI DINI GANGGUAN REFRAKSI MATA PADA ANAK-ANAK USIA SEKOLAH DASAR - Zayadi Zainuddin; Arif Ikhwandi; Mardhatilah Marsa (DHARMA RAFLESIA, 2018)
Eye refractive errors that are not handled seriously will affect the intellectual development of children. The learning process is stunted children can affect the quality, creativity, and productivity in the productive age. Early detection of refractive errors can be done with a simple eye. Its objective is to equip UKS teachers in practicing the use of Snellen chart as an ongoing screening program for the prevention of risks of children with visual impairments in children of primary school age. The method of this activity is done by providing direct training to the teachers, especially primary school UKS teachers to use the Snellen chart. Training activities and practice the use of Snellen chart for UKS teachers of primary schools in the district Taba Penanjung place smoothly as expected. Need governments to elementary schools were able to detect and follow up on children who experience eye refractive errors early on an ongoing basis. Keywords: refraction, Snellen chart, training